2019
DOI: 10.1007/s10142-019-00658-3
|View full text |Cite
|
Sign up to set email alerts
|

Combining CDKN1A gene expression and genome-wide SNPs in a twin cohort to gain insight into the heritability of individual radiosensitivity

Abstract: Individual variability in response to radiation exposure is recognised and has often been reported as important in treatment planning. Despite many efforts to identify biomarkers allowing the identification of radiation sensitive patients, it is not yet possible to distinguish them with certainty before the beginning of the radiotherapy treatment. A comprehensive analysis of genome-wide single-nucleotide polymorphisms (SNPs) and a transcriptional response to ionising radiation exposure in twins have the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 78 publications
0
15
0
Order By: Relevance
“…Unfortunately, the normal tissue around the targeted region is also affected by DNA damage from radiation, and must rely on DNA repair mechanisms for rehabilitation of cellular functions [ 8 ]. A recent twin-study has reported that certain SNPs and their transcriptomic influence are associated with individual radiation sensitivity and a heritability estimate of 66% [ 9 ]. Therefore, it is vital to understand genetics underlying molecular mechanisms involved in adverse effects of radiotherapy and individual genetic variations that may induce radiation sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the normal tissue around the targeted region is also affected by DNA damage from radiation, and must rely on DNA repair mechanisms for rehabilitation of cellular functions [ 8 ]. A recent twin-study has reported that certain SNPs and their transcriptomic influence are associated with individual radiation sensitivity and a heritability estimate of 66% [ 9 ]. Therefore, it is vital to understand genetics underlying molecular mechanisms involved in adverse effects of radiotherapy and individual genetic variations that may induce radiation sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have identified genetic variations involved in DNA repair pathways to be associated with overall radiotoxicity [ 3 , 10 ]. However, the role of altered gene expression [ 9 ] from aggregated single nucleotide polymorphisms (SNPs) remains elusive in radiotoxicity phenotypes (e.g., proctitis). Regulatory variants are SNPs within coding regions which contribute towards tissue – specific gene expression alterations leading to variations in the phenotypic spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of altered gene expression [9] from aggregated single nucleotide polymorphisms (SNPs) remains elusive in radiotoxicity phenotypes (e.g., proctitis).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the normal tissue around the targeted region is also affected by DNA damage from radiation, and must rely on DNA repair mechanisms for rehabilitation of cellular functions [8]. A recent twin-study has reported that certain SNPs and their transcriptomic in uence are associated with individual radiation sensitivity and a heritability estimate of 66% [9]. Therefore, it is vital to understand genetics underlying molecular mechanisms involved in adverse effects of radiotherapy and individual genetic variations that may induce radiation sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have identi ed genetic variations involved in DNA repair pathways to be associated with overall radiotoxicity [3,10]. However, the role of altered gene expression [9] from aggregated single nucleotide polymorphisms (SNPs) remains elusive in radiotoxicity phenotypes (e.g., proctitis). Regulatory variants are SNPs within coding regions which contribute towards tissue -speci c gene expression alterations leading to variations in the phenotypic spectrum.…”
Section: Introductionmentioning
confidence: 99%